2015
DOI: 10.1128/genomea.01289-15
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequences for Five Strains of Trabulsiella odontotermitis, Isolated from Heterotermes sp. Termite Gut

Abstract: Trabulsiella odontotermitis represents a novel species in the genus Trabulsiella with no complete genome reported yet. Here, we describe the draft genome sequences of five isolates from termites present in the north of Mexico, which have an interesting pool of genes related to cellulose degradation with biotechnological application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…isolated from the wood-feeding termite Heterotermes sp. showed the presence of an array of cellulolytic enzymes, suggesting their involvement in cellulose degradation within the digestive tract (Olvera-García et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…isolated from the wood-feeding termite Heterotermes sp. showed the presence of an array of cellulolytic enzymes, suggesting their involvement in cellulose degradation within the digestive tract (Olvera-García et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Suman et al [ 104 ] found the strain of IIPTG13 Trabulsiella also might play a role in the lignin degradation. Recently, Olvera-García et al [ 105 ] described the genome of five strains of Trabulsiella and found that this species has a pool of genes related to cellulose degradation. Maybe at the feed-out an aerobic microbial community capable of degrading cellulose settles down after the levels of soluble carbohydrates decrease.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, two genes were cloned from T. odontotermitis , and their expressed products (egl-FZYE and cel-FZYE), which exhibited endoglucanase and a β-glucosidase activity, respectively, were selected based on previous annotation of the T. odontotermitis genome [ 21 ]. The estimated masses of egl-FZYE and cel-FZYE were 42 and 55 kDa, respectively, which were similar to the values predicted by the ExPASy Bioinformatics Resources Portal [ 22 ] i.e., 41.5 and 55.4 kDa, respectively), whereas the estimated masses of the egl-FZYE and cel-FZYE fusion proteins were 70 and 83 kDa, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The sequences of the endoglucanase and ß-glucosidase genes were obtained from the genome annotation analyses performed for five T. odontotermitis strains isolated from the digestive tract of the termite Heterotermes sp. [ 21 ]. The coding sequences of both genes (omitting stop codons) were synthesized carrying the restriction sites for the NdeI and SapI enzymes at the 5′ and 3′ ends, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation